Gledalci - kdo so? - Maanen, Hans van (Amfiteater (Ljubljana), 2015)
When speculating on how theatre functions in a society, the most obvious questions are how many people make use of the theatre that is on offer and, subsequently, which parts of the population make use of what types of theatrical events. In this article, both questions are answered for the cities of Debrecen in Hungary, Groningen in the Netherlands, Tyneside in the United Kingdom and Tartu in Estonia. After explaining the research design within the STEP City Study and some methodological difficulties, we attempt to present a precise picture of the different audiences, their preferences and frequencies of theatre visits. Based on the data collected in these four cities, comparative conclusions may be drawn about the parts of the population which make use of the theatre supply in general and in more detail. One remarkable outcome is that in Groningen, 8.4% of the city population makes use of the professional theatre supply for adults, whereas in Tartu, this percentage is 20.7%.
Keywords: Debrecen; Europe; Evropa; gledališče; gledališko občinstvo; Groningen; international comparative theatre survey; mednarodne primerjave; STEP; Tartu; theater; theatre audience; Tyneside